2012
DOI: 10.1007/s00247-012-2444-9
|View full text |Cite
|
Sign up to set email alerts
|

An MRI system for imaging neonates in the NICU: initial feasibility study

Abstract: Our preliminary experience demonstrates the feasibility and potential of the neonatal MRI system to provide state-of-the-art MRI capabilities within the NICU. Advantages include overall reduced cost and site demands, lower acoustic noise, improved ease of access and reduced medical risk to the neonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 44 publications
0
66
0
1
Order By: Relevance
“…A small-footprint 1.5-T orthopedic MRI scanner (ONI Medical Systems, currently GE Healthcare, Waukesha, WI) was previously adapted for clinical use in our NICU (17)(18)(19); the scanner's 18-cm bore can accommodate infants weighting up to approximately 4,000 g. Using this scanner, standard axial three-dimensional fast gradient echo (FGRE) images were acquired in all 18 patients (repetition time/echo time [TR/TE] z7/1.9 ms; 10 8 flip angle; 18-20 cm field of view; 3 mm slice thickness; 5-10 averages). Additionally, fast spin echo (FrFSE) images were acquired for 10 patients (TR/TE 3,000/11.6 ms; 16 cm field of view; 3 mm slice thickness; echo train length 5) and Propeller images (TR/TE 3,750/32.5 ms; 16 cm field of view; 3 mm slice thickness; echo train length 10) were acquired for 11 patients.…”
Section: Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small-footprint 1.5-T orthopedic MRI scanner (ONI Medical Systems, currently GE Healthcare, Waukesha, WI) was previously adapted for clinical use in our NICU (17)(18)(19); the scanner's 18-cm bore can accommodate infants weighting up to approximately 4,000 g. Using this scanner, standard axial three-dimensional fast gradient echo (FGRE) images were acquired in all 18 patients (repetition time/echo time [TR/TE] z7/1.9 ms; 10 8 flip angle; 18-20 cm field of view; 3 mm slice thickness; 5-10 averages). Additionally, fast spin echo (FrFSE) images were acquired for 10 patients (TR/TE 3,000/11.6 ms; 16 cm field of view; 3 mm slice thickness; echo train length 5) and Propeller images (TR/TE 3,750/32.5 ms; 16 cm field of view; 3 mm slice thickness; echo train length 10) were acquired for 11 patients.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…Pulmonary MRI of the neonate is additionally confounded by small patient size and the delicate nature of transporting a NICU patient to the scanner. To overcome the latter two challenges, we extend the application of a unique, small footprint 1.5-T MRI scanner designed by our colleagues in the Imaging Research Center at Cincinnati Children's Hospital for installation and clinical use in our NICU (17)(18)(19) to image neonatal lungs. Using this scanner, commercial MRI sequences, and quantitative analysis, we demonstrate the ability of MRI to spatially map and quantify lung pathology associated with premature birth in quietly breathing neonates.…”
mentioning
confidence: 99%
“…A second report from the Hammersmith team specific to neonates with BPD found higher relative proton density in BPD patients versus controls and described 2 types of parenchymal abnormalities in BPD infants: focal high-density areas and low-density, cystlike abnormalities. 43 Colleagues at Cincinnati Children's Hospital Medical Center designed and modified a small-footprint 1.5-T orthopedic MRI scanner for use in the authors' NICU, [44][45][46] and they recently reported success imaging nonsedate, free-breathing BPD patients using this scanner and standard MRI pulse sequences. 47 Stark and significant differences in parenchymal signal intensity were observed in the BPD patients compared with full-term control NICU patients (Fig.…”
Section: Conventional 1 H Mrimentioning
confidence: 97%
“…Higher magnetic field strengths provide increased signal to noise which can be used to improve temporal and/or spatial resolution. However, 3T MRI also increases artifacts, such as susceptibility and chemical shift can be used in advanced imaging such as fMRI, SWI and MRS.(16,22,28,31-37)…”
Section: Improvements and Implications Of Increased Magnetic Field Stmentioning
confidence: 99%